Outcomes of a Provincial Myocardial Infarction Reperfusion Strategy: A Population-Based, Retrospective Cohort Study. Issue 5 (3rd October 2020) - Cook, Jolene; Carter, Alix; Goldstein, Judah; Travers, Andrew; Brown, Ryan; Swain, Janel; Jensen, Jan; Matheson, Kara; Cain, Ed; Lee, Tony
Abstract: Background: Fibrinolysis is an acceptable treatment for acute ST-segment elevation myocardial infarction (STEMI) when primary percutaneous coronary intervention (PCI) cannot be performed within 120 minutes. The American Heart Association has recommended Emergency Medical Services (EMS) interventions such as prehospital fibrinolysis (PHF), prehospital electrocardiogram (ECG), and hospital bypass direct to PCI center. Nova Scotia, Canada has incorporated these interventions into a unique province-wide approach to STEMI care. A retrospective cohort analysis comparing the primary outcome of 30-day mortality for patients receiving either prehospital or emergency department (ED) fibrinolysis (EDF) to patients transported directly by EMS from community or regional ED for primary PCI was conducted. Methods: This retrospective, population-based cohort study included all STEMI patients in Nova Scotia who survived to hospital admission from July 2011 through July 2013. Three provincial databases were used to collect demographic, 30-day mortality, hospital readmission, and rescue PCI data. The results were grouped and compared according to reperfusion strategy received: PHF, EDF, patients brought by ambulance via EMS direct to PCI (EMS to PCI), and ED to PCI (ED to PCI). Results: There were 1, 071 STEMI patients included with 145 PHF, 606 EDF, 98 EMS to PCI, and 222 ED to PCI. There were no significant differences in 30-day mortality across groups (n, %): PHF 5(3); EDF 36(6); EHS to PCI <5(2); and ED to PCI 10(4); P = .28. There was no significant difference in patients receiving fibrinolysis who underwent rescue PCI. Conclusions: Prehospital fibrinolysis incorporated into a province-wide approach to STEMI treatment is feasible with no observed difference in patient 30-day mortality outcomes observed.